High dielectric constant epoxy nanocomposites containing ZnO quantum dots decorated carbon nanotube. Issue 5 (10th August 2020) - Liu, Cong; Daneshvar, Farhad; Hawkins, Spencer; Kotaki, Masaya; Sue, Hung‐Jue
Abstract: Zinc oxide (ZnO) quantum dot (QD) decorated multi‐walled carbon nanotube (MWCNT) hybrid was utilized in the fabrication of high dielectric constant epoxy nanocomposites. Because of the shielding effect of ZnO QD, the well‐dispersed epoxy hybrid nanocomposites exhibit frequency insensitive high dielectric constant as well as greatly reduced dielectric loss. With only 1.5 wt% of MWCNT addition, the epoxy/MWCNT‐ZnO nanocomposite possesses dielectric constant as high as 31 and dielectric loss as low as 0.01 at 1 kHz. In addition, the epoxy nanocomposite exhibits greatly enhanced tensile properties. The role of ZnO QD decorated MWCNT in the preparation and property improvement of multi‐functional polymer nanocomposites is discussed. Abstract :